1994
DOI: 10.3758/bf03205307
|View full text |Cite
|
Sign up to set email alerts
|

Phonological codes are early sources of constraint in visual semantic categorization

Abstract: Two experiments were directed at early phonological activation in the semantic categorization task. In Experiment 1, briefly exposed targets homophonic to category exemplars (ROWS for the category A FLOWER), and their graphemic controls (ROBS), were judged for category membership with and without a backward pattern mask. False positives were greater for ROWS than ROBS to the same degree under both unmasked and masked conditions. In Experiment 2, false positives were examined in the semantic categorization task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…This does not reflect a task-specific strategy in which phonology is utilised solely for supporting judgements of lexicality. The effects of phonology can also be seen in tasks involving semantic categorisation of homophones and pseudohomophones (Lesch & Pollatsek, 1998;Peter & Turvey, 1994;Van Orden, 1987;Van Orden, Johnston, & Hale, 1988). Analogous effects have been found in priming studies, which show that phonological and semantic information can be accessed from masked word and nonword primes with display durations of as little as 50 ms. (Perfetti & Bell, 1991;Ferrand & Grainger, 1992).…”
Section: The Role Of Phonologymentioning
confidence: 72%
“…This does not reflect a task-specific strategy in which phonology is utilised solely for supporting judgements of lexicality. The effects of phonology can also be seen in tasks involving semantic categorisation of homophones and pseudohomophones (Lesch & Pollatsek, 1998;Peter & Turvey, 1994;Van Orden, 1987;Van Orden, Johnston, & Hale, 1988). Analogous effects have been found in priming studies, which show that phonological and semantic information can be accessed from masked word and nonword primes with display durations of as little as 50 ms. (Perfetti & Bell, 1991;Ferrand & Grainger, 1992).…”
Section: The Role Of Phonologymentioning
confidence: 72%
“…The PsH disadvantage in lexical decision can be used as a marker for the influence of phonological information during silent reading. That is, if phonology is a primary constraint during silent reading (e.g., Lukatela & Turvey, 1994;Peter & Turvey, 1994;Rayner, Sereno, Lesch, & Pollatsek, 1995;Van Orden, 1987;1991;Ziegler & Jacobs, 1995), then it should be harder to reject PsHs like BRANE than controls like BRATE. Therefore, if German children employ more efficient phonological recoding processes at the grapheme-phoneme level, as suggested by the pattern of accuracy advantages found in Experiment 1, it can be predicted that PsH interference effects will be stronger in lexical decision for German children than for English children.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Van. Orden (1987) and others (e.g., Jared & Seidenberg, 199 I;Peter & Turvey, 1994) have found that when participants make speeded judgments concerning whether a target word (e.g., rose) is a member of a prespecified category (e.g.,jlower), homophone foils (e.g., rows) and pseudohomophone foils (e.g., roze) give rise to more false-positive errors than do orthographically matched control foils (e.g., robs). Importantly, given that the costs associated with homophony would be eliminated if readers chose not to engage phonological processes, the fact that homophony does interfere with performance in these tasks strongly suggests that phonological processes are carried out automatically.…”
mentioning
confidence: 99%